Background and Activities of the Samsung Ombudsperson Commission in Korea - Cheolsoo Lee; Seong-Kyu Kang; Hyunwook Kim; Inhee Kim (Korean Society for Preventive Medicine, 2019)
Objectives: The Samsung Ombudsperson Commission was launched as an independent third-party institution following an agreement among Samsung Electronics, Supporters for Health and Right of People in Semiconductor Industry (Banolim in Korean, an independent NGO), and the Family Compensation Committee, in accordance with the industry accident prevention measure required by the settlement committee to address the issues related to employees who allegedly died from leukemia and other diseases as a result of working at Samsung's semiconductor production facilities. Methods: The Commission has carried out a comprehensive range of activities to review and evaluate the status of the company's occupational accidents management system, as well as occupational safety and health risk management within its facilities. Results: Based on the results of this review, termed a comprehensive diagnosis, the Commission presented action plans for improvement to strengthen the company's existing safety and health management system and to effectively address uncertain risks in this area going forward. Conclusions: The Commission will monitor the execution of the suggested tasks and provide advice and guidance to ensure that Samsung's semiconductor and liquid crystal display production lines are safer.